2016
DOI: 10.7314/apjcp.2016.17.s3.293
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Killing of Breast Cancer Cells by IgYs Produced Against a Small 21 Aminoacid Epitope of the Human TRAIL-2 Receptor

Abstract: TRAIL, tumor necrosis factor (TNF)-related apoptosis-inducing ligand belongs to one of important cytokine superfamilIES, tumor necrosis factor (TNFα) . TRAIL-2 receptor agonists activate several cell signaling pathways in cells in different manners and could lead to apoptosis or necrosis. Agonistic egg yolk antibodies like IgY which have been developed in a selective manner could activate TRAIL death receptors such as TRAIL-2 (DR5) and thus apoptosis signaling. We here investigated induction of apoptosis in hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Following this rationale, Amirijavidv et al produced highly specific IgY against a sequence of 21 amino acids present on the ectodomain of the TRAIL (TNF-related apoptosis-inducing ligand) receptor TRAIL-R2 (DR5). The antibodies bound to the amino acid sequence and activated the DR5 receptors in human breast cancer cells MCF7, acting as a TRAIL agonist and inducing apoptosis [87]. IgY against other receptors, such as the HER2 receptor, was tested coupled to single walled carbon nanotubes (SWNTs) and specifically detected the HER2 receptors on the surface of SK-BR-3 cells.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Following this rationale, Amirijavidv et al produced highly specific IgY against a sequence of 21 amino acids present on the ectodomain of the TRAIL (TNF-related apoptosis-inducing ligand) receptor TRAIL-R2 (DR5). The antibodies bound to the amino acid sequence and activated the DR5 receptors in human breast cancer cells MCF7, acting as a TRAIL agonist and inducing apoptosis [87]. IgY against other receptors, such as the HER2 receptor, was tested coupled to single walled carbon nanotubes (SWNTs) and specifically detected the HER2 receptors on the surface of SK-BR-3 cells.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Information related to the pharmacokinetics of IgY is currently scarce. The available data come from animal models with the application of sublethal doses of xenogeneic snake venom [ 60 ]. In these studies, IgY was shown to have a wide and rapid distribution in the animal body, including muscles and brain parenchyma [ 61 ].…”
Section: Pharmacokinetics and Pharmacodynamics Of Igymentioning
confidence: 99%
“…Similarly, the entry of IgY into the brain across the blood–brain barrier was demonstrated, and it could neutralize the poison and act as an antivenom. The IgY antibodies specifically recognized the venom and as previously mentioned, did not activate the complement system, suggesting the possibility of safe re-administration until the resolution of intoxication symptoms in animals not developing ADE [ 60 , 61 ]. Since oral administration of IgY in humans has been shown to be effective and without side-effects, its parenteral administration needs further investigation to determine its safety, tolerability, and efficacy [ 62 , 63 , 64 ].…”
Section: Pharmacokinetics and Pharmacodynamics Of Igymentioning
confidence: 99%
“…This approach using chicken igy has shown promising results in killing breast cancer cells. 121,122 14.3.3.1.3 Egg Proteins and Diagnosis of Cancer. in parallel, the immunoglobulin y strategy to produce antibodies against cancerous biomarkers has been extensively used to develop tools (eliSA/immunohistochemistry) that contribute to the diagnosis/prognosis of the disease.…”
Section: Egg Proteins In Targeting Cancer Cellsmentioning
confidence: 99%